PENGEMBANGAN MEDIA FLIPBOOK DIGITAL BERBASIS STORYTELLING KONTEKSTUAL PADA MATERI SISTEM PENGLIHATAN UNTUK SISWA KELAS V SEKOLAH DASAR - Najwa Kareenina; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the learning process of Ilmu Pengetahuan Alam dan Sosial (IPAS) in elementary schools which is still dominated by lecture methods and text-based learning, causing students to experience difficulties in understanding abstract concepts, especially the visual system material. This study aims to develop a contextual storytelling-based digital flipbook on the visual system material for fifth-grade elementary school students. This research used the Research and Development (R&D) method with the 4D development model limited to the develop stage. Data collection techniques were carried out through literature studies and validation questionnaires. The subjects of this research were media experts and material experts. The data analysis technique used descriptive quantitative analysis. The results showed that the developed media obtained a feasibility percentage of 83% from media experts and 87,06% from material experts with the category of “very feasible”. Therefore, the contextual storytelling-based digital flipbook is feasible to be used as an IPAS learning media on visual system material.